Non-Coding RNAs in the Regulation of Doxorubicin-Induced Cardiotoxicity - Mengyao Sun; Il-Man Kim; Lei Yang (Biomolecules)
Doxorubicin, a commonly prescribed chemotherapeutic drug in clinical practice, is associated with severe cardiotoxicity that restricts its long-term use in cancer treatment. Recent studies have highlighted the critical roles of non-coding RNAs (ncRNAs) in the regulation of doxorubicin-induced cardiotoxicity (DIC). Notably, ncRNAs, including microRNAs, long non-coding RNAs, and circular RNAs, display critical functions in various DIC-associated cellular processes, such as cell death, oxidative stress, and mitochondrial dysfunction, all of which contribute to the pathophysiology of DIC. Accumulated evidence indicates that ncRNAs regulate gene expression by interacting with DNAs, RNAs, proteins, and lipids, presenting a potential avenue to alleviate the adverse effects of doxorubicin on hearts. This review discusses the emerging research progress focusing on the molecular mechanisms by which ncRNAs regulate DIC. Understanding the complicated and essential roles of ncRNAs in DIC could thus pave the way for developing novel cardioprotective strategies.